2022
DOI: 10.3389/fphys.2022.845634
|View full text |Cite
|
Sign up to set email alerts
|

Functional Heterogeneity of Cell Populations Increases Robustness of Pacemaker Function in a Numerical Model of the Sinoatrial Node Tissue

Abstract: Each heartbeat is initiated by specialized pacemaker cells operating within the sinoatrial node (SAN). While individual cells within SAN tissue exhibit substantial heterogeneity of their electrophysiological parameters and Ca cycling, the role of this heterogeneity for cardiac pacemaker function remains mainly unknown. Here we investigated the problem numerically in a 25 × 25 square grid of connected coupled-clock Maltsev-Lakatta cell models. The tissue models were populated by cells with different degree of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 75 publications
3
23
0
Order By: Relevance
“…More recent studies, from that group and others [9,51,52], have confirmed the existence of dormant SA nodal cells in tissue under a variety of conditions. Our results, along with similar recent modeling studies [38], demonstrate that when dormant cells are coupled with a minority of spontaneous cells, the tissue can exhibit stable electrical activity even in the absence of sympathetic stimulation. Our results also suggest that relatively large percentages of dormant cells can indeed be consistent with normal pacemaker function at the tissue level due to the protective effects of heterogeneity and intercellular coupling.…”
Section: Are Dormant Cells Present Inside the Sinoatrial Node?supporting
confidence: 87%
“…More recent studies, from that group and others [9,51,52], have confirmed the existence of dormant SA nodal cells in tissue under a variety of conditions. Our results, along with similar recent modeling studies [38], demonstrate that when dormant cells are coupled with a minority of spontaneous cells, the tissue can exhibit stable electrical activity even in the absence of sympathetic stimulation. Our results also suggest that relatively large percentages of dormant cells can indeed be consistent with normal pacemaker function at the tissue level due to the protective effects of heterogeneity and intercellular coupling.…”
Section: Are Dormant Cells Present Inside the Sinoatrial Node?supporting
confidence: 87%
“…APs) within SAN tissue, e.g. via a stochastic resonance (Clancy and Santana, 2020;Grainger et al, 2021;Guarina et al, 2022), or a phase transition-like process each cycle (Weiss and Qu, 2020;Maltsev et al, 2022a). Thus, following this logic, in addition to the tonic influence or simple “wake-up” function under stress, dormant cells can be in fact functionally active generating important subthreshold signals.…”
Section: Discussionmentioning
confidence: 99%
“…What are potential roles and benefits of the new pacemaker mechanism? It can keep the system alive at the edge of criticality in heterogenous SAN tissue (Campana et al, 2022;Maltsev et al, 2022a), e.g. in aging and disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations